2013
DOI: 10.1136/annrheumdis-2012-202868
|View full text |Cite
|
Sign up to set email alerts
|

The fibrin-derived citrullinated peptide β60–74Cit60,72,74bears the major ACPA epitope recognised by the rheumatoid arthritis-specific anticitrullinated fibrinogen autoantibodies and anti-CCP2 antibodies

Abstract: Autoantibodies reactive to α36-50Cit₃₈,₄₂ and β60-74Cit₆₀,₇₂,₇₄ form two distinct, non-overlapping subfamilies of ACPA that, together, cover practically all the ACPA reactivity to citrullinated fibrinogen and to CCP2 antigens. In established RA, anti-β60-74Cit₆₀,₇₂,₇₄ autoantibodies show diagnostic indexes similar to those of anti-CCP2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
4
27
0
1
Order By: Relevance
“…It allowed the assay to reach a very good diagnosis performance for RA similar to that of AhFibA detection. Although the diagnostic performance obtained with this peptide needs to be confirmed on a larger cohort, this result shows that almost all AhFibA-positive sera recognized the bME and thus emphasized our previous conclusion that b60-74 bore the immunodominant epitope recognized by AhFibA (32,48).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…It allowed the assay to reach a very good diagnosis performance for RA similar to that of AhFibA detection. Although the diagnostic performance obtained with this peptide needs to be confirmed on a larger cohort, this result shows that almost all AhFibA-positive sera recognized the bME and thus emphasized our previous conclusion that b60-74 bore the immunodominant epitope recognized by AhFibA (32,48).…”
Section: Discussionsupporting
confidence: 72%
“…AhFibA and Abs against the nonbiotinylated a36-50 and b60-74 reference peptides were detected by ELISA as previously described (23,32,33,35). AhFibA titers were considered as the OD obtained on citrullinated fibrin.…”
Section: Elisa Quantification Of Autoantibodies Directed Toward Citrumentioning
confidence: 99%
See 1 more Smart Citation
“…Assays using peptides that contain citrulline (deiminated arginine residues) are highly predictive and specific for the diagnosis of rheumatoid arthritis [16]. Recently, two distinct subfamilies of anti-citrulline antibodies against citrullinated fibrin-derived peptides were identified [17]. In addition, two citrullinated histone H4 peptides were shown to be preferentially recognized by autoantibodies present in the majority of patients with rheumatoid arthritis, but not in SLE [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have identified and validated some of the cit-Fib epitopes in RA using different approaches [8, 1620]. Cit-Fib has also been verified as an ACPA target in patients with RA throughout the world [2123] with recognition of the α subunit peptide 36-52 and the β subunit peptide 60-74 being the most prominent.…”
Section: Introductionmentioning
confidence: 99%